Kepimpinan dalam kumpulan keil yang bersifat Ad Hoc (sementara): satu kajian kes - Ratnah, Mohamad Yunus (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study aims to explore the leadership aspect in small ad hoc group. This research identified the leadership characters and leadership style in small ad hoc groups. Besides that, the research also uncovers the conflicts that occur within group and identify solutions to solve those problems. Other factors that possible influence the success or failure of small ad hoc group was also identified. This study focused on small ad hoc groups among student and these groups are either moderate or excellent in term of their achievement. Nine informants were been interviewed including three leaders, three group members from the excellent group and three group members from the moderate group. This research found that ten characters of successful leaders in a small ad hoc group. The research also found that three leadership styles were commonly used by leaders in the groups. Seven elements that caused conflicts among the small ad hoc group member and seven suggestions were also proposed to handle the conflict in small ad hoc group. There are several factors that contribute to the success of small group and factors that also contribute to the failure of small group. However, there are some factors that were found to be similar to what by other researchers had discovered in their studies.